Dual‐Wavelength Irradiation and Dox Delivery for Cancer Cell Ablation with Photocatalytic Pr Doped TiO2/NGO Hybrid Nanocomposite. Issue 12 (17th June 2015) - Jang, Hongje; Choi, Myung‐Ho; Yim, Yeajee; Kim, Young‐Kwan; Min, Dal‐Hee
<x xml:space="preserve">Abstract</x> Herein, hybrid nanocomposite of praseodymium doped TiO2 nanocrystals and graphene oxide nanosheets are prepared by facile hydrothermal treatment. As‐synthesized Pr‐TiO2/NGO hybrid nanocomposite exhibits enhanced photocatalytic activity under visible light irradiation by the intact graphene oxide and doped lanthanide mediated band gap narrowing compared to TiO2. Moreover, high payload and controlled release of doxorubicin by charge reversal of hybrid nanocomposite at endosomal pH and near‐infrared irradiation mediated efficient photothermal conversion provide highly favorable features in therapeutic applications. Through the combination of these three distinctive therapeutic modalities, highly efficient trimodal cancer cell ablation is demonstrated.